Tofacitinib facilitates the expansion of myeloid-derived suppressor cells and ameliorates interstitial lung disease in SKG mice - Sendo, Sho (Arthritis Res Ther, 2019)
BACKGROUND: Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is a sometimes life-threatening complication in RA patients. SKG mice develop not only arthritis but also an ILD resembling RA-ILD. We previously reported that tofacitinib, a JAK inhibitor, facilitates the expansion of myeloid-derived suppressor cells (MDSCs) and ameliorates arthritis in SKG mice. The aim of this study was to elucidate the effect of tofacitinib on the ILD in SKG mice. METHODS: We assessed the effect of tofacitinib on the zymosan (Zym)-induced ILD in SKG mice histologically and examined the cells infiltrating the lung by flow cytometry. The effects of lung MDSCs on T cell proliferation and Th17 cell differentiation were assessed in vitro. We also evaluated the effects of tofacitinib on MDSCs and dendritic cells in vitro. RESULTS: Tofacitinib significantly suppressed the progression of ILD compared to the control SKG mice. The MDSCs were increased, while Th17 cells, group 1 innate lymphoid cells (ILC1s), and GM-CSF+ILCs were decreased in the lungs of tofacitinib-treated mice. MDSCs isolated from the inflamed lungs suppressed T cell proliferation and Th17 cell differentiation in vitro. Tofacitinib promoted MDSC expansion and suppressed bone marrow-derived dendritic cell (BMDC) differentiation in vitro. CONCLUSION: Tofacitinib facilitates the expansion of MDSCs in the lung and ameliorates ILD in SKG mice. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13075-019-1963-2) contains supplementary material, which is available to authorized users.